1992
DOI: 10.1002/pon.2960010206
|View full text |Cite
|
Sign up to set email alerts
|

Changes in marital and sexual functioning in long‐term survivors and their spouses: Testicular cancer versus hodgkin's disease

Abstract: This study compares the effects of the cancer experience on various aspects of marital and sexual functioning (e.g., communication, emotional support, body image, sexual satisfaction and frequency) for two groups of long‐term cancer survivors (testicular cancer and Hodgkin's disease) and their spouses. Comparisons between the two patient groups showed significantly more survivors of Hodgkin's disease than testicular cancer reporting the emergence of special issues and changes in the marital relationship. No di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
2

Year Published

1997
1997
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 30 publications
1
44
0
2
Order By: Relevance
“…Although attention has been paid to sexual functioning in TCSs themselves, very little research has been done into the sexual satisfaction of their partners. Two reports have been published on sexual functioning, in the same group of 34 TCSs and spouses mentioned above [7,10]. TCSs and their spouses reported a decrease in sexual frequency since the illness and treatment.…”
Section: Marital and Sexual Satisfaction In Testicular Cancer Survivomentioning
confidence: 92%
See 1 more Smart Citation
“…Although attention has been paid to sexual functioning in TCSs themselves, very little research has been done into the sexual satisfaction of their partners. Two reports have been published on sexual functioning, in the same group of 34 TCSs and spouses mentioned above [7,10]. TCSs and their spouses reported a decrease in sexual frequency since the illness and treatment.…”
Section: Marital and Sexual Satisfaction In Testicular Cancer Survivomentioning
confidence: 92%
“…Little research has been done into marital satisfaction of men with cancer and their female partners, and only two studies have addressed this issue in TCSs and their spouses. These two studies [6,10] (on the same group of TCSs and spouses) showed that couples felt the relationship became more tightly bonded and stronger following the confrontation with TC. However, it should be noted that the results were based on a fairly small sample (n=34) and on a group survivors who had completed treatment an average of 4 years prior to the assessment, thus not showing insight into long-term adjustment.…”
Section: Marital and Sexual Satisfaction In Testicular Cancer Survivomentioning
confidence: 99%
“…Treatment for TC is known to have repercussions on marital functioning [23]. The qualitatively stronger studies reported that most TCSs did not experience a change in the relationship with their partner after their experience with TC [40,41] and that treatment groups did not differ in their responses to questions about changes in the partner relationship since treatment [47].…”
Section: Marital Functioningmentioning
confidence: 99%
“…Several studies have measured the acute affective response to the diagnosis of cancer and patients' psycho- logical reactions to relapse [1,5,7,15]. These studies on mixed populations of patients have revealed a prevalence of affective distress varying between 23% and 47%.…”
Section: Introductionmentioning
confidence: 99%